PROBLEMATIKA JUAL BELI PERTALITE DAN PERTAMAX ECERAN DALAM TINJAUAN FIQIH - Ika Nur Solikah; Ahmad Asrof Fitri; Irvan Iswandi (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2022)
One of the most common commodity traded in rural areas is pertalite and pertamax. This study examines: (1) how is the practice of retailing pertalite and pertamax, with case study in Mekarjaya village and (2) what is status of the trading of retailed pertalite and pertamax in Islamic Law perspective. This research is a qualitative research. Data were collected through interviews, observation, and documentation. Results of this research are: (1) Liter measuring system was used in retailing pertalite and pertamax in Mekarjaya village. Sellers usually buy pertalite and pertamax at gas stations using jerry cans. The purchased pertalite and pertamax are poured into a large bucket, then measured using a one-liter stainless volume measuring can and poured into a used bottle using a funnel tool. (2) Majority of the sales in Mekarjaya village had met requirements of legal trading in Islamic Law. In Islamic perspective, there are three laws regarding the retail: First, absolutely legal, if amount of the fuel is in accordance with contract. Second, legal with conditional circumstance, if there is a willingness from the buyer for the lack of measurement in pertalite and pertamax volume because of something natural like evaporation. Third, illegal, if the seller deliberately reduces the dose in order to find more profit.